Pupil dilation predicts individual self-regulation success across domains - Silvia U. Maier (Nature Portfolio, 2021)
Abstract Multiple theories have proposed that increasing central arousal through the brain’s locus coeruleus—norepinephrine system may facilitate cognitive control and memory. However, the role of the arousal system in emotion regulation is less well understood. Pupil diameter is a proxy to infer upon the central arousal state. We employed an emotion regulation paradigm with a combination of design features that allowed us to dissociate regulation from emotional arousal in the pupil diameter time course of 34 healthy adults. Pupil diameter increase during regulation predicted individual differences in emotion regulation success beyond task difficulty. Moreover, the extent of this individual regulatory arousal boost predicted performance in another self-control task, dietary health challenges. Participants who harnessed more regulation-associated arousal during emotion regulation were also more successful in choosing healthier foods. These results suggest that a common arousal-based facilitation mechanism may support an individual’s self-control across domains.